Upaya Kepala Sekolah dalam Meningkatkan Kinerja Guru: Systematic Literature Review (SLR) - Fikri Adha; Kasman Kasman; Rizki Fadilah; Annisa Fitri; Luluk Khoiriyah (Indo Publishing, 2026)
Teacher performance is a crucial factor in determining the success of the educational process in schools. High-performing teachers are able to effectively implement learning, thereby improving the quality of student learning outcomes. In efforts to improve teacher performance, principals play a strategic role as educational leaders responsible for managing, fostering, and developing human resources within the school environment. This study aims to examine various efforts made by principals to improve teacher performance based on published research findings. The method used in this study was a Systematic Literature Review (SLR), analyzing various relevant scientific articles from national journals published in recent years. The review process involved identification, selection, evaluation, and synthesis of articles that met the research criteria. The results indicate that several key efforts undertaken by principals to improve teacher performance include academic supervision, work motivation, continuous professional development, creating a conducive school climate, and providing rewards and performance evaluations. These efforts have been shown to have a positive impact on improving teacher competence, discipline, responsibility, and professionalism. Therefore, effective principal leadership is a crucial factor in supporting improved teacher performance and the quality of education in schools.